Pete the cat. Super Pete - Dean, Kim, 1969-; Dean, James, 1957- (Pete the cat., 2020)
Donning a cape and sneakers, Pete the Cat assumes his groovy alter ego, Super Pete, and takes down bad guys using crimefighting gadgets from his secret underground lair.